Knowledge and Compliance with Universal Precautions amongst Nurses in Selected Hospitals in Imo State, Nigeria - Udemba N. C.; Ezeama M.C (Poltekkes Kemenkes Yogyakarta, 2021)
This study assessed the knowledge and compliance with universal precautions amongst nurses in selected hospitals in Imo State, Nigeria. Four research questions and objectives guided the study. The study adopted a cross sectional descriptive design. Stratified and simple random sampling techniques were adopted in selecting sample size of 290 which was determined by the use of Taro Yamane. Data were collected using a self-developed structured questionnaire validated by the project supervisor. The Data were analyzed using descriptive statistics and Statistical Package for Social Sciences (SPSS) version 21.0.The findings revealed that majority of the nurses possessed high knowledge of universal precautions. An overall mean value of 3.26, ±0.9 showed majority of nurses has high level of compliance with universal precautions. The result further revealed that overall mean of 2.58,and ±1.034agreed that there are many barriers to compliance with universal precautions which includes, lack of available equipment, overall mean 2.83 and ±.98.The study also revealed that overall mean of 2.22 and ± 0.518 showed that nurses always practices different universal precautions. There exists no significant relationship between level of knowledge and compliance (x2=2.347; P>0.05, c=094; Sig = 672). Socio-demographic characteristics and level of compliance (x2=220;P>0.05, c=029; Sig = .974). Recommendations were made, pertinent among which are there is urgent need for targeted mass education and mobilization of nurses on the public health implications of non-compliance with Universal Precautions. Nursing and self-help groups in the campaign against barriers to compliance with universal precautions should be formed; professional guidelines on universal precaution for healthcare providers should be defined. Lastly compliance with Universal Precautions should be encouraged among nurses irrespective of their socio-economic profiles.